Optimalisasi Investasi Pendidikan: Menggali Konsep Dan Standar Fundamental Dalam Pembiayaan - Effendy, Evita Nor; Rizkia Putri, Refika Pricila; Sania, Nia; Prihantini, Prihantini (Universitas Hamzanwadi, 2024)
Education is something that must be taken by all people in Indonesia regardless of their background. Education makes a person have insight and knowledge that can be used as a guide to be applied in everyday life. In this case, facilities and infrastructure in supporting education are important for the continuity of the teaching and learning process carried out by an educational institution, such as a school. This study aims to analyze more deeply the concepts and fundamental standards in financing with the optimization of investment in education. Through qualitative research methods with an analytical descriptive approach, it can further explore the financing that can be obtained by schools to support the success of student learning. Due to the facts that occur in the field, it is often found that schools have inadequate facilities or teaching materials that support other than teacher books, are still lacking or even non-existent. Therefore, it is important to know the management of financing by optimizing education investment, so that it is hoped that in the future the services provided by schools related to something that supports the learning process will be evenly distributed and can be felt by all schools, so that it can also have an impact on student learning outcomes.